A High‐Throughput Workflow for CRISPR/Cas9 Mediated Combinatorial Promoter Replacements and Phenotype Characterization in Yeast. Issue 9 (22nd May 2018) - Kuivanen, Joosu; Holmström, Sami; Lehtinen, Birgitta; Penttilä, Merja; Jäntti, Jussi
Abstract : Due to the rapidly increasing sequence information on gene variants generated by evolution and the improved abilities to engineer novel biological activities, microbial cells can be evolved for the production of a growing spectrum of compounds. For high productivity, efficient carbon channeling toward the end product is a key element. In large scale production systems the genetic modifications that ensure optimal performance cannot be dependent on plasmid‐based regulators, but need to be engineered stably into the host genome. Here, a CRISPR/Cas9 mediated high‐throughput workflow for combinatorial and multiplexed replacement of native promoters with synthetic promoters and the following high‐throughput phenotype characterization in the yeast Saccharomyces cerevisiae is described. The workflow is demonstrated with three central metabolic genes, ZWF1, PGI1, and TKL1 encoding a glucose‐6‐phosphate dehydrogenase, phosphoglucose isomerase, and transketolase, respectively. The synthetic promoter donor DNA libraries are generated by PCR and transformed to yeast cells. A 50% efficiency is achieved for simultaneous replacement at three individual loci using short 60‐bp flanking homology sequences in the donor promoters. Phenotypic strain characterization is validated and demonstrated using liquid handling automation and 150 μL cultivation volume in 96‐well plate format. The established workflow offers a robust platform for automated engineering and improvement of yeast strains. Abstract : Engineered microbial cells can be used for the production of chemicals. For high productivity, efficient carbon channeling toward the end product is a key element. In this study, the authors describe a CRISPR/Cas9 mediated high‐throughput workflow for combinatorial and multiplexed replacement of native promoters with synthetic promoters and the following high‐throughput phenotype characterization in the yeast Saccharomyces cerevisiae . The workflow provides a basis for similar high‐throughput engineering and characterization tasks in yeast.